DEVELOPING READING MATERIALS FOR PHYSICAL EDUCATION STUDENTS - Dina Ayu Puspita Wardani; Yazid Basthomi; Sunaryo Sunaryo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
This present study intends to develop reading materials for physical education students’ of STKIP PGRI Jombang as an effort in improving students’ English ability especially on reading skill. The research and development procedures of this present study are obtained by adaptation the combination models of Borg and Gall (1983), Dick and Carey (2001) and Hyland (2003). It is adapted simplifier into four stages, those are: (1) need analysis; (2) developing material; (3) validation; (4) revisions. The material developed was based on the real field condition which is suited to the students’ and the lecturer’s need. It is also considered by the syllabus used by the lecturer.Penelitian ini bertujuan untuk mengembangkan materi reading untuk mahasiswa jurusan pendidikan jasmani dan kesehatan di STKIP PGRI Jombang sebagi salah satu usaha untuk meningkatkan kemampuan bahasa Inggris mahasiswa khususnya pada reading skill. Metode pengembangan yang digunakan dalam penelitian diadaptasi dari Borg and Gall (1983), Dick and Carey (2001) and Hyland (2003) yang dikombinasikan dan disederhanakan menjadi empat langkah, meliputi (1) analisis kebutuhan; (2) pengembangan materi; (3) validasi; (4) revisi. Materi yang dikembangkan disesuaikan dengan kebutuhan mahasiswa dan dosen. Pengembangan materi juga didasarkan pada silabus yang digunakan oleh dosen.